Body as expression of psychiatric distress: insights from restrictive eating disorders, non-suicidal self-injuries, and suicide attempts - Pratile, Diletta Cristina; Orlandi, Marika; Mensi, Martina Maria (Frontiers in Psychology, 2025)
IntroductionAdolescence is a developmental period marked by vulnerabilities where psychological distress often manifests through the body. Restrictive Eating Disorders (REDs), Non-Suicidal Self-Injury (NSSI), and Suicide Attempts (SAs) represent distinct yet overlapping expressions of this phenomenon.MethodsThis cross-sectional study compared 60 adolescents (20 for each group) aged 12–18 across these groups using a comprehensive multimethod assessment, including the Kiddie Schedule for Affective Disorders and Schizophrenia (K-SADS-PL), the Structured Clinical Interview for DSM-5 Personality Disorders (SCID-5-PD), and the Rorschach Performance Assessment System (R-PAS).ResultsThe RED group exhibited the highest obsessive-compulsive symptoms and distorted interpersonal representations linked to perfectionism and body image concerns. R-PAS scores highlighted disorganized thinking and maladaptive self and other perceptions. The NSSI group displayed significant borderline traits, emotion regulation deficits, and impressionistic responses, with elevated R-PAS indices reflecting interpersonal defensiveness and vulnerability to emotional distress. The SA group showed severe depressive symptoms, dysregulation, and impaired thought organization, with the lowest functional scores (CGAS). Across all groups, adverse childhood experiences and distorted interpretations of stimuli emerged as common factors, supporting shared vulnerability.DiscussionThis study provides a nuanced understanding of bodily expressions of psychological distress by integrating structured interviews, personality assessments, and performance-based tools. These findings emphasize the importance of tailored diagnostic and therapeutic strategies that address the unique and overlapping characteristics of these groups, advancing precision in adolescent mental health care.